KAJIAN PRODUCTION EMPHASIS , PENGEMBANGAN KARIR PROTEAN, DAN KOMPENSASI SOSIAL PADA KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Dean Subhan Saleh; Salman Imbari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
One of the success key of a company isincreasing the competitiveness of human resources. The important concept that is recognized as a key for a superior human resources is the right people in the right place at the right time. The low performance from the employer can result in low productivity ( profit) of the company. The performance of employer must be noticed by the company, because the performance of employer can give direct impact in all performance of the company. The motive for this study for test and analyzed the impact of Production Emphasis, the development , the development of Carier Protean and Social Compensation of the performance employer with Job Satisfaction for mediation variabel. The research was conducted on PT. Subang Autocomp Indonesia employer and use multiple regresi linier analysis, SPSS 24 version and path analysis. The result of the study indicate partially the Production Emphasis, Carier Protean development and Social Compensation variabel showing a significant increase in employee performance. And simultan the Production Emphasis, Carier Protean development, and Social Compensation variabel on employee performance mediated by job satisfaction that have a significant effect. While the contribution of variabel and variabel intermediation depends on employee performance by 67% while the remaining 33% by other factors